Przeciw tyranii Hegla, albo przechadzka po francuskiej myśli ponowoczesnej - Kwiek, Marek (My University, 1997)
The text deals with a constant and pervading influence exerted by Hegel on pre- and postwar French philosophy (1930-1960) thus far, however, as it became an object of deep disagreement and criticism by the next, postmodern generation of philosophers. Thus, the text is about the generation of A. Kojeve, J. Hyppolite. G. Bataille, reading and commenting on Hegel — mainly from The Phenomenology of Mind — against which the generation of J. Derrida, M. Foucault and G. Deleuze protested. While Hegel was the master thinker for the former generation, for the latter he was a philosopher from whom it was necessary to get liberated with Nietzsche's help. The question put forward is the following: what kind of Hegel was it that the generation of Hyppolite's pupils turned so unanimously against? The question about that Hegel — read mainly from the renowned Chapter IV of The Phenomenology.... devoted to dialectic oj mastery and slavery — will help us here to solve the problem of complicated relations between Hegel and postmodern French thinkers. We think that it is impossible to understand today's French anti-Hegelian scenery without the question who that Hegel was and in what circumstances he appeared.
Keywords: Francuski Hegel; francuski Nietzsche; nietzscheanizm; heglizm; Alexandre Kojeve; Fenomenologia ducha; Pierre Klossowski; Gilles Deleuze; Georges Bataille; powojenna filozofia francuska; intelektualiści; filozofia a polityka; zaamgażowanie polityczne; polis; praxis; rewolucja; zmienianie świata; dialektyka pana i niewolnika; Jean Hyppolite; panowanie i niewolnictwo; mistrzowie myślenia; myśl francuska; Michel Foucault